Equilibrium of argon plasma particles at high pressure - Faisal Zakky; Reeky Fardinata; Muhammad Safwan Abd Aziz (Science, Technology, and Communication Journal, 2023)
The density value and plasma reaction rate are the physical quantities needed to produce plasma. Both are used to estimate the heat energy and operating time of the plasma. Argon plasma at atmospheric pressure is widely used in industry. Density values and plasma reaction rates were obtained by computational modeling using the continuity equation and the Arrhenius equation obtained from experimental data. Five argon species were used in this research including Ar*, Ar+, Ar2+, Ar, and electron. Plasma equilibrium occurs in time intervals of 10-12 – 10-3 seconds with a temperature of 2 eV. The overall thermal argon plasma equilibrium density ranges within the interval 109 – 1016 m-3. The value of the fastest reaction rate obtained is equal to 2.482 × 104 m-3.s-1 until the smallest reaction rate is obtained equal to 14.613 × 10-34 m-3.s-1.